Innovation des pratiques, Maître Formateur et accompagnement par la recherche - Jean-Michel Perez; Géraldine Suau (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
enOur article deals with teachers in Master Teacher Training Schools (MTTS), considered essential in the French education system for their teaching and training mission and subject to an institutional context that gives a significant weight to their commitment to pedagogical innovation. We propose to use a case study to examine the praxeological development of a teacher trainer who has been little studied in the context of a research training program based on the framework of the anthropological theory of didactics (Chevallard, 1998).